MANAJEMEN KEPEGAWAIAN DALAM MENINGKATKAN KINERJA APARATUR SIPIL DI SEKRETARIAT DAERAH PROVINSI KALIMANTAN TIMUR - Mahezha Jennar (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This study examines the Civil Service Management in Improving Performance In the State Civil Administrative Secretariat of the Province of East Kalimantan, which is motivated by the uneven performance of the State Civil Apparatus contained in the Secretariat of the Province of East Kalimantan. Based on the results obtained from the conclusion that the implementation process of the personnel management at the Secretariat of the Province of East Kalimantan has been performing well, it is apparent from Has the implementation of elements of management, coaching an employee is working, coaching effectiveness and efficiency that has been accomplished in the process of improving the performance Apparatus State Civil , staffing is carried out by using a selection of office and process assessment center in accordance with the legislation in force, taking disciplinary action for employees has been implemented in accordance with the regulations in force , the implementation of activities of physical and mental development for the whole Apataur State Civil environment of the Secretariat of the Province of East Kalimantan and the establishment of good working relationships between superiors and subordinates